Screening of antihyperglycaemic activity of medicinal plant extracts instreptozocin-induced type 2 diabetic mice - Xuan Thu, Nguyen Thi; Duc Long, Dang (Vietnam Journal of Biotechnology, 2020)
Traditional plant used for treatment of diabetes has shown a surging interest in the last few decades. The purpose of this study is to evaluate the effect of 70% (v/v) ethanolic extracts of several untested herbal sources, such as papaya leaves, papaya seeds, fig fruits, fruits of Xanthium strumarium, and leaves of Gomphrena celosioides on blood glucose levels of streptozocin (STZ)-induced type 2 diabetic mice. The results proved that diabetic mice treated with the extracts of papaya seeds, papaya leaves and fig fruits showed significant reduction of the blood glucose levels at a dose of 500 mg/kg body weight when compared to control. Antihyperglycemic activity of the papaya leaves (52.38%) and papaya seeds extracts (53.16%) were significantly higher than the extract of fig fruits (27.90%). Furthermore, the α-amylase inhibition assay showed that the extracts of papaya seeds (58,63 ± 0,06 μg/ml), papaya leaves (34,28 ± 0,06 μg/mL) and fig fruits (79,24 ± 0,83 μg/mL) exhibited 50% α-amylase inhibition activity at the mentioned concentrations. The α-glucosidase IC50 of the extracts of the papaya seeds, papaya leaves and fig fruits were found to be 24.36 ± 0,29, 27,60 ± 0,43 and 106,44 ± 1,54 respectively. The results of the study indicate the potential of these extracts to manage hyperglycemia. The histopathological study of the papaya seeds extract has shown to ameliorate the streptozocin-induced histological damage of islets of Langerhans in the pancreas.